CD44v6 specific CAR-NK cells for targeted immunotherapy of head and neck squamous cell carcinoma - Ciulean, Ioana Sonya; Fischer, Joe; Quaiser, Andrea; Bach, Christoph; Abken, Hinrich; Tretbar, Uta Sandy; Fricke, Stephan; Koehl, Ulrike; Schmiedel, Dominik; Grunwald, Thomas (Frontiers in Immunology, 2023)
Head and neck squamous cell carcinoma (HNSCC) is a major challenge for current therapies. CAR-T cells have shown promising results in blood cancers, however, their effectiveness against solid tumors remains a hurdle. Recently, CD44v6-directed CAR-T cells demonstrated efficacy in controlling tumor growth in multiple myeloma and solid tumors such as HNSCC, lung and ovarian adenocarcinomas. Apart from CAR-T cells, CAR-NK cells offer a safe and allogenic alternative to autologous CAR-T cell therapy. In this paper, we investigated the capacity of CAR-NK cells redirected against CD44v6 to execute cytotoxicity against HNSCC. Anti-CD44v6 CAR-NK cells were generated from healthy donor peripheral blood-derived NK cells using gamma retroviral vectors (gRVs). The NK cell transduction was optimized by exploring virus envelope proteins derived from the baboon endogenous virus envelope (BaEV), feline leukemia virus (FeLV, termed RD114-TR) and gibbon ape leukemia virus (GaLV), respectively. BaEV pseudotyped gRVs induced the highest transduction rate compared to RD114-TR and GaLV envelopes as measured by EGFP and surface CAR expression of transduced NK cells. CAR-NK cells showed a two-to threefold increase in killing efficacy against various HNSCC cell lines compared to unmodified, cytokine-expanded primary NK cells. Anti-CD44v6 CAR-NK cells were effective in eliminating tumor cell lines with high and low CD44v6 expression levels. Overall, the improved cytotoxicity of CAR-NK cells holds promise for a therapeutic option for the treatment of HNSCC. However, further preclinical trials are necessary to test in vivo 2 This is a provisional file, not the final typeset article efficacy and safety, as well to optimize the treatment regimen of anti-CD44v6 CAR-NK cells against solid tumors.